Dilemmas in anticoagulation and use of inferior vena cava filters in venous thromboembolism; a survey of Respiratory Physicians, Haematologists and Medical Oncologists and a review of the literature. (1st January 2021) - Craven, Philip; Daly, Ciara; Sikotra, Nisha; Clay, Tim; Gabbay, Eli
Abstract : Twenty percent of patients with Cancer Associated Thrombosis receive an inferior vena cava filter annually. Insertion is guided by practice guidelines, which do not specify or discuss the use of inferior vena cava filters in malignancy. Adherence to these guidelines is known to be variable. We aimed to see if there was consistent management of venous thromboembolism among Medical Oncologists/Haematologists and Respiratory Physicians, with respect to inferior vena cava filter use in the setting of suspected and confirmed malignancy. Medical Oncologists, Haematologists and Respiratory Physicians were surveyed with four theoretical cases. Case 1 concerns a patient who develops a pulmonary embolism following spinal surgery. Cases 2 and 4 explore the use of inferior vena cava filters in the setting of malignancy. Case 3 covers the role of inferior vena cava filters in recurrent thrombosis despite systemic anticoagulation. There were 56 responses, 32 (57%) Respiratory Physicians and 24 (43%) Haematologists/Oncologists. Respiratory Physicians were significantly more likely to insert an inferior vena cava filter in case 1 ( p = 0.04) whilst Haematologists/Medical Oncologists were more likely to insert an inferior vena cava filter in case 3 ( p = 0.03). No significant differences were found in cases 2 and 4. There were significant disparities in terms of type and timing of anticoagulation. Consistency of recommendations with guidelines was variable likely in part because guidelines are themselves inconsistent. The heterogeneity in responses highlights the variations in venous thromboembolism management, especially in Cancer Associated Thrombosis. International Societies should consider addressing inferior vena cava filter use specifically in the setting of Cancer Associated Thrombosis. Collaboration between interested specialities would assist in developing consistent, evidence‐based guidelines for the use of inferior vena cava filters in the management of venous thromboembolism.